A comparison of drug transport in pulmonary absorption models: isolated perfused rat lungs, respiratory epithelial cell lines and primary cell culture - Bosquillon, Cynthia; Madlova, Michaela; Patel, Nilesh; Clear, Nicola; Forbes, Ben (Springer, 2017)
Purpose